Aktivitas Afrodisiaka Fraksi dari Ekstrak Etanol 70% Daun Katuk (Sauropus androgynus (L). Merr) Pada Tikus Putih Jantan - Rusdi, Numlil Khaira; Hikmawanti, Ni Putu Ermi; Maifitrianti, Maifitrianti; Ulfah, Yuanita Sofiana; Annisa, Ayyoehan Tiara (Pharmaceutical Sciences and Research, 2018)
Decreased of libido is illustrated with disinterest in sexual activity caused by erectile dysfunction, impotence, and infertility. It can be treated by aphrodisiac agents. Katuk or Sauropus androgynus (L). Merr has long been used as a medicinal plant. The aim of this research was to evaluate which fraction of katuk leaf ethanol extract that had the aphrodisiac activity with parameters of climbing, introduction and the weight of testicular and seminal vesicle of male rat. Sprague-Dawley male rats as animals model divided into five groups: the normal control group, the positive control group (X-gra®), the n-hexane, ethyl acetate and water fraction groups in which each fraction group given a dose of 11.85 mg/kg body weight. The number of climbing and introductions were calculated on 0, 1st, 3th, and 5th day. The data were tested statistically with one-way ANOVA test followed by Tukey test. The weight of testicular and seminal vesicle of male rat were observed on the 15th day. Previously, rats were anesthetized using ketamine and then performed surgery. The results showed that the n-hexane fraction (11.85 mg/kg body weight) increased libido with the average number of climbing was 16.5 times and the average number of introductions was 27.75 times. It was also able to increase the weight of testicular and seminal vesicle of male rat compare to positive control (X-gra® 51.37 mg/kg body weight). The compounds contained in n-hexane fraction are terpenoids and steroids.